2020
DOI: 10.1111/cas.14695
|View full text |Cite
|
Sign up to set email alerts
|

Gene amplification of YB‐1 in castration‐resistant prostate cancer in association with aberrant androgen receptor expression

Abstract: Most prostate cancers are initially dependent on androgens for tumor growth, and show good response to androgen-deprivation therapy (ADT). 1 However, most of these cancers eventually recur during ADT in a castration-resistant manner and are defined as castration-resistant prostate cancer (CRPC). 2 Despite the recognition of a variety of molecular mechanisms for progression to castration resistance, androgen receptor (AR)-dependent mechanisms, such as AR overexpression and AR variant expression, are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…DdPCR was performed as described previously (Shiota et al, 2021). Primers and probes for ddPCR were as follows: HSD3B1 (dHsaCNS478433216) and RPP30 (dHsaCP2500350; BioRad Laboratories).…”
Section: Droplet Digital Pcr (Ddpcr) Quantitative Real-time Pcr and W...mentioning
confidence: 99%
“…DdPCR was performed as described previously (Shiota et al, 2021). Primers and probes for ddPCR were as follows: HSD3B1 (dHsaCNS478433216) and RPP30 (dHsaCP2500350; BioRad Laboratories).…”
Section: Droplet Digital Pcr (Ddpcr) Quantitative Real-time Pcr and W...mentioning
confidence: 99%
“…Some quinolone derivatives (Figure 1) were used to evaluate the possible interaction with both the androgen receptor and RSK-4 as follows: 1= 1-ethyl-2(1H)-quinolone [19] 2= 1-methyl-6-nitro-2(1H)-quinolone [20] 3= 2-(2-quinolinyl)-1-[4-(trifluoromethyl)phenyl]ethanone [21] 4= 2-chloro-1-(8-hydroxy-5-quinolinyl)ethanone [22] 5= 2-cyano-3-phenyl-N-(quinoline-3-yl)acrylamide [23] 6= 4-chloro-6-(3,4-dihydro-1(2h)-quinolinyl)-2-pyrimidinamine [24] 7= 4-cyclohexyl-2(1h)-quinolone [25] 8= 4-Hydroxy-1-methyl-2(1H)-quinolone [26] 9= 5,7-dibromo-8-quinolinyl 4-nitrobenzoate [27] 10=6-methoxy-8-[(2-furanylmethyl)amino]-4-methyl-5-(3trifluoromethylphenyloxy)quinolone [28] 11= 6-Quinolinyl trifluoromethanesulfonate [29] 12= 8-(Bromomethyl)quinoline [30] 13= 8-quinolinyl n-(3-bromophenyl)carbamate [31] 14=Cipriploxacine(1-cyclopropyl-6-fluoro-4-oxo-7-piperazine-1-ylquinoline-3carboxylic acid) [32] 15 = 2-(Bromomethyl)quinolone [33] 16 = 2-(Trifluoromethyl)quinolone [34] 17= N4-(7-Chloro-4-quinolinyl)-N1,N1-dimethyl-1,4-pentanediamine [35] 18= 8-Hydroxyquinoline [36] 19=Flumequine (7-fluoro-12-methyl-4-oxo-1-azatricyclo[7.3.1.0] [5,13] trideca-2,5,7,9(13)-tetraene-3-carboxylic acid) [37]…”
Section: Methodsmentioning
confidence: 99%
“…[10] On the other hand, some studies suggest that ribosomal S6 p90 kinase (RSK 1-4), which belongs to the group of highly conserved Ser/Thr kinases, [11] has been related to an increase in prostate cancer. For example, a study showed the Inhibition of RSK and YB-1 (Y-box; regulates androgen receptor expression) [12,13] signaling enhances the anti-cancer effect of enzalutamide in prostate cancer. [14] In addition, a report showed that S6 PMD-026 drug acts as an inhibitor of RSK in combination with enzalutamide in castration-resistant prostate cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…12 In the nucleus, YB-1 acts as a transcription and splicing factor, modulating the expression of its target genes. 13 YB-1 has been implicated in various physiological and pathological processes, including cell proliferation, fatty acid synthesis, antifibrotic effects, and cancer progression. 3,[13][14][15] Additionally, YB-1 has been found to interact with other proteins, such as Elongin BC and transportin 1, which can affect its stability, assembly of protein complexes, and subcellular localization.…”
Section: Introductionmentioning
confidence: 99%
“…13 YB-1 has been implicated in various physiological and pathological processes, including cell proliferation, fatty acid synthesis, antifibrotic effects, and cancer progression. 3,[13][14][15] Additionally, YB-1 has been found to interact with other proteins, such as Elongin BC and transportin 1, which can affect its stability, assembly of protein complexes, and subcellular localization. 16,17 Overall, YB-1 is a multifunctional protein that plays a critical role in various cellular processes and has implications in disease development and progression.…”
Section: Introductionmentioning
confidence: 99%